(untitled) (Review of Croatian History, 2021)
In this paper authors analyze the prosecution of the widespread chant “Marjane, Marjane” during 1980’s in Socialist Republic of Croatia. Widespread version of the chant regime has proscribed, declaring it a form of hostile or anti-state act. Individuals who would sing any of prohibited versions would be mostly subjugated to political felony procedure and sentenced to prison.